2015
DOI: 10.1530/eje-15-0282
|View full text |Cite
|
Sign up to set email alerts
|

Breast cancer risk in hyperprolactinemia: a population-based cohort study and meta-analysis of the literature

Abstract: Objective: To enhance the precision of the risk estimate for breast cancer in hyperprolactinemia patients by collecting more data and pooling our results with available data from former studies in a meta-analysis. Design: Population-based cohort study and meta-analysis of the literature. Methods: Using nationwide registries, we identified all patients with a first-time diagnosis of hyperprolactinemia during 1994-2012 including those with a new breast cancer diagnoses after the start of follow-up. We calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 15 publications
0
10
0
2
Order By: Relevance
“…Some studies suggest an independent risk of suicide (Brugnoli 2012). Although some studies have found an association between hyperprolactinaemia and breast cancers (Tworoger 2007, 2013), meta-analysis has failed to confirm this (Dekkers 2015). Acne and mild hirsutism can develop, due to the relative increase of androgenic compared with oestrogenic activity.…”
Section: Clinical Consequences Of Hyperprolactinaemiamentioning
confidence: 99%
“…Some studies suggest an independent risk of suicide (Brugnoli 2012). Although some studies have found an association between hyperprolactinaemia and breast cancers (Tworoger 2007, 2013), meta-analysis has failed to confirm this (Dekkers 2015). Acne and mild hirsutism can develop, due to the relative increase of androgenic compared with oestrogenic activity.…”
Section: Clinical Consequences Of Hyperprolactinaemiamentioning
confidence: 99%
“…Aside from these, idiopathic hyperprolactinaemia is not uncommon. 3 Data from case series and cross-sectional studies in patients with hyperprolactinaemia suggest that prolactinomas and other pituitary tumour types (35-70%) and idiopathic hyperprolactinaemia (28-46%) are the most common categories, [9][10][11][12][13][14] but the majority of studies excluded drug-induced cases. The large number of commonly prescribed medications associated with hyperprolactinaemia suggests it is likely to occur frequently in the population, although its frequency has rarely been documented; Vilar et al reported a prevalence of 14Á5% drug-induced cases from a sample of patients identified at ten endocrine centres in Brazil.…”
Section: Introductionmentioning
confidence: 99%
“…A small increased overall cancer risk (HR = 1.31, 95% CI: 1.02–1.68) was reported by Berinder et al from a population-based cohort study of 969 patients with visible pituitary adenomas and/or diagnosis of hyperprolactinaemia followed for 14 years but no increased risk of breast cancer was observed (12). However, several large case-controlled and population-based cohort studies have failed to show any increased risk of breast cancer (9, 11, 14). As in our study, Berinder et al .…”
Section: Discussionmentioning
confidence: 99%
“…Controversy exists as to whether hyperprolactinaemia may be associated with heart valve disease (including that related to the use of dopamine agonist therapy), cardiovascular risk factors or cardiovascular mortality (4, 5, 6, 7). Results from epidemiologic studies that have examined the relationship between prolactin and all-cause cancer or breast cancer have also given inconsistent results (8, 9, 10, 11, 12, 13, 14, 15, 16). Similarly, there are no consistent correlations reported between prolactin levels and bone loss or autoimmune diseases; thus, the clinical significance of hyperprolactinaemia in these patients remains unclear (17, 18, 19, 20, 21, 22, 23, 24, 25, 26).…”
Section: Introductionmentioning
confidence: 99%